(untitled) (Research, Society and Development, 2021)
The açaizeiro (Euterpe oleracea Mart.) Is one of the main crops disseminated in the Amazon region with economic, social and environmental importance. The present work aimed to evaluate the use of polyethylene bag and tube with different volumes in the production of açaizeiro seedlings. The trial was conducted in the experimental field of the Federal University of the South and Southeast of Pará between April and November 2018, in Marabá, Pará. The experimental design used was a completely randomized design with 2 treatments and 4 repetitions. The evaluated containers were perforated black bags with a capacity of 2800 cm3 and tubes with a capacity of 265 cm3. The cultivar evaluated was BRS - Pará. After germination, the seedlings were transplanted into containers with substrate containing 60% sand, 20% sawdust and 20% tanned manure. The evaluations were made every 30 days after the transplant, counting the number of leaves emitted, the height of the plant and the diameter of the collect. The determination of total dry matter was carried out at 120 days after transplantation. The data were subjected to analysis of variance and the means compared by Tukey’s test at 5% and Dickson’s quality index (IQD). The parameters height and total dry mass were significantly influenced by the volume of the container. The diameter of the collect and number of leaves of the seedlings produced in the bags and tubes did not differ statistically. Açaí seedlings are best produced in in perforated black bags with a capacity of 2800 cm3.